About Modern Factors of Yakut Identity at the Turn of the XX–XXI Centuries - Daria G. Bragina (Ethnic Culture, 2022)
In the conditions of the historically established ethnic diversity in the Republic of Sakha (Yakutia), the complex development of market relations and the strengthening of the role of the ethnic factor, the problems of ethno-social adaptation of the indigenous population arises. The purpose of the article is to study the structure of a person's self-identification and to research various forms of identity such as ethno-cultural, linguistic and ethnic. One of the main sources for studying the problems of ethnicity was both various statistical materials, data from an ethno-sociological survey, and field ethnographic materials obtained by the author of the article in the course of expeditionary and stationary work in the uluses of the republic over the last quarter of the XX century – the beginning of the XXI century. When writing the work, the author applied both methods of field research in order to collect initial material, as well as theoretical and methodological ones. The article concludes that if there is a problem with the functioning of the Yakut language and its loss by a part of the urban Yakut population, it does not lead to the loss of Yakut identity. On the contrary, partly the loss of their native language by people of Yakut nationality, as it turned out, leads to the strengthening of their ethno-cultural identity. The dynamic of the number of Yakuts shows that the ethnic factor plays an important role in the identification of a person. The results of the work confirm the thesis that ethnicity, compensating for the weakening of civic identity, becomes a defining stratifying category, acquiring the ethnopolitical rank. In general, despite the influence of various factors, the materials of ethno-sociological studies in Yakutia showed a high degree of manifestation of both ethnic and ethno-cultural identity, and partly linguistic.